The Relationship between Authoritarian Leadership and Employees’ Deviant Workplace Behaviors: The Mediating Effects of Psychological Contract Violation and Organizational Cynicism - Jiang, Hongyan; Chen, Yang; Sun, Peizhen; Yang, Jun (Frontiers in Psychology, 2017)
This study investigated the relationship between authoritarian leadership and employees’ deviant workplace behaviors, as well as the mediating effects of psychological contract violation and organizational cynicism. A cross-sectional survey was conducted among 391 manufacturing workers in a northern city of China. Structural equation modeling was performed to test the theory-driven models. The results showed that the relationship between authoritarian leadership and employees’ deviant workplace behaviors was mediated by organizational cynicism. Moreover, this relationship was also sequentially mediated by psychological contract violation and organizational cynicism. This research unveiled psychological contract violation and organizational cynicism as underlying mechanism that explained the link between authoritarian leadership and employees’ deviant workplace behaviors.